Tinjauan Pustaka : Promosi Kesehatan dan Gizi Pada Populasi Migran: Literature Review: Health and Nutrition Promotion in Migrant Populations - Ira Yunianti; Setianingrum, Wulan; Fitriana, Destia Ika; Puspikawati, Septa Indra (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2026)
Background: Migrants are a vulnerable group experiencing various health and nutritional problems due to environmental changes, limited access to health services, cultural barriers, and acculturation stress. Therefore, health and nutrition promotion are important strategies to improve the quality of life and well-being of migrant populations. Objectives: To identify the forms of health and nutrition promotion interventions in migrant populations, assess their effectiveness, and explore barriers to their implementation. Methods: This study used a Systematic Literature Review method based on the PRISMA 2020 guidelines. Article searches were conducted through the Google Scholar database using the keywords